Driving Sales in the Platform Economy: The Role of Taste and Promotion in Chaipao Asiok Purchases through GrabFood - Wijaya, Michael Kurniawan; Sinaga, Hommy Dorthy Ellyany; Nasution, Lisa Elianti (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the economic influence of taste and promotional strategies on consumer purchase decisions for Chaipao Asiok through the GrabFood application. As food delivery platforms become increasingly dominant in the digital economy, understanding key consumer drivers such as sensory experience (taste) and marketing efforts (promotion) is critical for business sustainability. The study population comprises all Chaipao Asiok consumers who ordered via the GrabFood application from 2020 to 2024. A total of 130 respondents were selected using purposive sampling. Data were collected through questionnaires, interviews, and documentation. The analytical method employed was multiple linear regression. The findings reveal that both taste and promotion have a positive and statistically significant impact on consumer purchase decisions. These results highlight the economic value of strategic flavor development and promotional engagement in enhancing consumer behavior within the food delivery ecosystem.